THE ROLE AND SIGNIFICANCE OF GAME METHODS IN ENGLISH TEACHING (Journal of Universal Science Research, 2023)
This article talks about the use of various interesting game methods in teaching English. At the same time, information is given about the importance of the game method for the development of the mind of young people.